2010
DOI: 10.1111/j.1360-0443.2009.02890.x
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness‐based treatments for co‐occurring depression and substance use disorders: what can we learn from the brain?

Abstract: Both depression and substance use disorders represent major global public health concerns and are often co-occurring. Although there are ongoing discoveries regarding the pathophysiology and treatment of each condition, common mechanisms and effective treatments for co-occurring depression and substance abuse remain elusive. Mindfulness training has recently been shown to benefit both depression and substance use disorders, suggesting that this approach may target common behavioral and neurobiological processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 124 publications
1
96
0
3
Order By: Relevance
“…For example, through its attentional focus, individuals learn to become more aware of habit-linked, minimally conscious affective states and bodily sensations (e.g. lowlevel craving), thus "de-automating" this largely habitual process (Brewer, Bowen, Smith, Marlatt, & Potenza, 2010;Kabat-Zinn et al, 1985;Teasdale, Segal, & Williams, 1995). In fact, a recent study showed that mindfulness training was associated with improved performance on the Stroop task, suggesting that this training may help to bring even basic, automatic reactions under more conscious, cognitive control (Moore & Malinowski, 2009).…”
Section: How Does Mindfulness Training Work? Mindfulness Training Maymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, through its attentional focus, individuals learn to become more aware of habit-linked, minimally conscious affective states and bodily sensations (e.g. lowlevel craving), thus "de-automating" this largely habitual process (Brewer, Bowen, Smith, Marlatt, & Potenza, 2010;Kabat-Zinn et al, 1985;Teasdale, Segal, & Williams, 1995). In fact, a recent study showed that mindfulness training was associated with improved performance on the Stroop task, suggesting that this training may help to bring even basic, automatic reactions under more conscious, cognitive control (Moore & Malinowski, 2009).…”
Section: How Does Mindfulness Training Work? Mindfulness Training Maymentioning
confidence: 99%
“…As noted above, it is the habituated affective bias underlying emotional reactivity that fuels further rounds of craving and habituation. Thus, with attenuation of this affective bias, no further fuel is added to the fire, ultimately leading to smoking cessation Brewer et al, 2010). However, studies that directly test these hypotheses are needed.…”
Section: How Does Mindfulness Training Work? Mindfulness Training Maymentioning
confidence: 99%
“…Trait Mindfulness has been thought to be a naturally occurring difference among individuals or a dispositional trait 24 that can be developed through meditative practices and mindfulness-based interventions 19,23 . Individuals with high levels of trait mindfulness are theorized to be better able to view aversive experiences as being transient and to be less likely to engage in substance use behaviors as a means of coping with such experiences 20,39,40 .…”
Section: Introductionmentioning
confidence: 99%
“…Both may be helped by the attention training of mindfulness and learning acceptance. It has been suggested then that mindfulness may be of particular use where there are co-morbid mental health problems with substance misuse [51]. Some of the mindfulness trials, especially with DBT and ACT, have been with co-morbid populations [44,52,53].…”
Section: Mindfulness For Dual Diagnosismentioning
confidence: 99%